MR/CT atlas of anatomy [ a comprehensive digital sectional imaging library - Küper, Klaus; Georg Thieme Verlag (Stuttgart, Germany) (Stuttgart, Germany : Georg Thieme Verlag, 2001)
Shows digital sectional imaging anatomy in more than 3,000 MRI and CT scans, with over 150,000 individually labeled anatomic structures. Provides the anatomic information needed to acquire confidence in the evaluation of sectional anatomy
Title from disc label
System requirements: 486 CPU or higher; 20 MB free hard drive space; Windows 95/98 or Windows NT/2000; CD-ROM drive; 1024x768x256 color graphics
System requirements: Apple Macintosh; 20 MB free hard drive space; Mac OS Version 8 (8.1 or higher) or Mac OS-9;CD-ROM drive; 1024x768x256 color graphics
In English, German, Italian, French, Spanish, and Portuguese (Brazilian and European)
Keywords: Anatomy, Regional -- Atlases; Magnetic resonance imaging -- Atlases; Tomography, X-Ray Computed -- Atlases